ANALYSIS OF NURSE ABILITY IN IDENTIFYING CLINICAL RISK: LITERATURE REVIEW - Eka Yufi Septriana Candra; Dodi Wijaya; Nurfika Asmaningrum (UPT Penerbitan Universitas Jember, 2023)
Background: Patient safety is a top priority in hospital health care today, and the role of nurses in preventing and reducing risks, errors, and injuries is a top priority. Nurses are required to have various abilities that must be mastered in providing nursing care to patients. This study aims to identify factors that affect the ability of nurses to identify clinical risks. Method: A literature review that uses the PRISMA protocol in selecting articles and the Critical Appraisal Checklist in assessing article quality. Three databases are used to search articles with selected keywords from Medical Subject Headings (MeSH) combined with the Boolean operator Results: 10 selected articles in this study were further studied with relevant topics, and the results of the literature review stated that two main factors could influence the ability of nurses to identify clinical risks, including intrinsic factors and extrinsic factors. Intrinsic factors come from within the nurse such as knowledge and competence, psychological pressure, and experience of the nurse, while the extrinsic factors found include effective communication, teamwork, organizational support, leadership style, and work environment. Conclusions: the researchers concluded that the main factor that can affect the ability of nurses to identify clinical risks is effective communication.